ANALISIS KIMIA 6 JENIS KAYU JAWA BARAT - Jacob Ando (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The result of chemical analyses of 6 wood species from West Java is presented in this report. The analyses comprised of determination of cellulose, lignin, pentosan and extractive contents.The result shows that specific gravity ranges from 0.40 to 0.47, cellulose content from 45.4 to 60.6 percent, lignin from 22.5 to 33,2 percent, pentosan from 15,1 to 18, 7 percent and extractive from 0.8 to 2.7 percent.